Pengembangan dan Validasi Skala Cognitive Dissonance: Confirmatory Factor Analysis dan Composite Reliability - Mahmud Junianto; Yoga Aji Nugraha; Dika Setiagraha; Anddrean Yoga Pratama Duri; Kaisar Az Zaky; Ayu Zela Destriana Zendrato (Universitas Ngudi Waluyo, 2026)
This study aims to develop and validate a cognitive dissonance measurement tool in preschool tutoring institutions. The study population consisted of parents of children attending tutoring institutions in Palembang City, Indonesia. The study sample consisted of 71 parents selected using a simple random sampling technique. The development of the cognitive dissonance scale refers to Festinger's theory which consists of three dimensions, namely concern for agreement, purchasing discretion, and emotional. The data analysis process was carried out using the 2nd Confirmatory Factor Analysis (2nd CFA) approach with the help of the Smart-PLS application version 4.1.1.8 to test the validity and reliability of the measuring instrument. The results showed that there were 9 items declared valid with a Composite Reliability value of 0.863 and an Average Variance Extracted (AVE) of 0.709. Based on these results, the developed measuring instrument was declared valid and reliable in measuring cognitive dissonance in tutoring institutions. Practically, this measuring instrument is expected to help educational institutions in improving service quality, customer satisfaction, and customer loyalty. Meanwhile, theoretically, this measuring instrument is expected to be used in research that discusses cognitive dissonance. Abstrak Penelitian ini bertujuan untuk mengembangkan serta memvalidasi alat ukur cognitive dissonance pada konteks lembaga bimbingan belajar pre-school. Populasi penelitian terdiri dari orang tua anak yang mengikuti lembaga bimbingan belajar di Kota Palembang, Indonesia. Sampel penelitian berjumlah 71 orang tua yang dipilih menggunakan teknik simple random sampling. Pengembangan skala cognitive dissonance mengacu pada teori Festinger yang terdiri dari tiga dimensi, yaitu concern over deal, wisdom of purchase, dan emotional. Proses analisis data dilakukan menggunakan pendekatan 2nd Confirmatory Factor Analysis (2nd CFA) dengan bantuan aplikasi Smart-PLS versi 4.1.1.8 untuk menguji validitas dan reliabilitas alat ukur. Hasil penelitian menunjukkan bahwa terdapat 9 item yang dinyatakan valid dengan nilai composite reliability sebesar 0.863 dan Average Variance Extracted (AVE) sebesar 0.709. Berdasarkan hasil tersebut, alat ukur yang dikembangkan dinyatakan valid dan reliabel dalam mengukur cognitive dissonance pada lembaga bimbingan belajar. Secara praktis alat ukur ini diharapkan dapat membantu lembaga pendidikan dalam meningkatkan kualitas layanan, kepuasan konsumen, serta loyalitas pelanggan. Sedangkan secara teoritis, alat ukur ini diharapkan dapat digunakan dalam penelitian yang membahas tentang cognitive dissonance.